Competency Gaps in Islamic Finance Education: Evidence from PLS SEM - Munadiati; Anis Kurlillah (FEBI IAIN Langsa, 2026)
We investigated the alignment between academic preparation in Islamic Financial Management (MKS) programs and industry expectations in Aceh, Indonesia. Using Partial Least Squares Structural Equation Modeling (PLS‑SEM) on survey data from 74 alumni employed in Islamic Financial Institutions (LKIs), we tested how perceptions of Islamic Higher Education Institutions (PTKIs) and student self‑assessments influence LKI evaluations and quantified the effect of a latent Competency Gap. The structural model reveals that PTKI Perception significantly enhances LKI Evaluation (β = 0.342, p = 0.002), as does Student Self‑Assessment (β = 0.287, p = 0.005). Conversely, the Competency Gap, capturing shortfalls in sharia‑based product knowledge, risk management, and technical banking operations, exerts a significant negative effect on LKI Evaluation (β = −0.215, p = 0.041). These findings confirm that while PTKIs build strong conceptual foundations, lecture‑dominated pedagogy, partial implementation of Outcome‑Based Education, and limited experiential learning fail to develop applied competencies. We recommend curriculum reform grounded in outcome‑based design, integration of applied modules, case‑based projects, practitioner involvement, certified internships, and curriculum co‑design with LKIs. These measures can produce graduates who are both conceptually grounded and operationally competent, thereby strengthening governance quality and sharia compliance in Indonesia’s Islamic finance sector.